2018
DOI: 10.4081/jphia.2018.772
|View full text |Cite
|
Sign up to set email alerts
|

The role of health insurance in the coverage of oral health care in Senegal

Abstract: Oral diseases costs are among the most expensive health care benefits. In Senegal, households contribute up to 37.6% of the national health spending through direct payments. The aim of this work was to study the role of health insurance in the coverage of oral health care in Senegal. The study was based on health insurance agents and policyholders. The study reveals that oral health care coverage through health insurance still does not meet requirements for treatment of oral infections. In financial terms, ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…27 The reasons seem related to their low level of oral health perception or concern. 28,29 Men did not appear to use dental services more often after the health insurance expansion. 6 Annual dental scaling has been covered by insurance since 2013 for everyone aged ≥20 years.…”
Section: Discussionmentioning
confidence: 88%
“…27 The reasons seem related to their low level of oral health perception or concern. 28,29 Men did not appear to use dental services more often after the health insurance expansion. 6 Annual dental scaling has been covered by insurance since 2013 for everyone aged ≥20 years.…”
Section: Discussionmentioning
confidence: 88%
“…Dental treatment can be costly for an average Burundian family. Implementing policies to ensure affordability and accessibility of dental services can reduce barriers to oral healthcare, as safety nets, insurance coverage, and public health initiatives are not reported [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a study carried out in Senegal on the financial accessibility of health care showed that these difficulties were related to the lack of information of insured persons on the covered care and the inadequacy of the covered care that did not meet the needs of the insured [20]. Indeed, oral health care accounts for a significant portion of the health portfolio of insurance companies because of its perceived high cost [21]. For financial profitability, some care (prosthetic and orthodontic care) is poorly or not reimbursed by them.…”
Section: Discussionmentioning
confidence: 99%
“…This situation encourages some people to forego oral health care. Finally, insurance does not meet their health needs [21].…”
Section: Discussionmentioning
confidence: 99%